15. ANALYSIS OF SOME FACTORS RELATED NURSES’AWARENESS OF PATIENT SAFETY OF AT UNIVERSITY HOSPITAL MEDICINE AND PHARMACY, HANOI NATIONAL UNIVERSITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Patient safety is the prevention of errors that can cause harm to patients during treatment and care [7]. Internal safety is also an attribute of the medical industry, it minimizes incidents and maximizes recovery from incidents [5].Objective: Analyze a number of factors related to the awareness of patient safety of nurses at the University of Medicine and Pharmacy Hospital, Hanoi National University in 2023.Method: Cross-sectional description, with analysis.Results: Reasonable arrangement of daily work plays the most important role in valuing patient safety (β= 0.595), followed by good department management and handling unsafe incidents good patients (β= 0.384 and 0.378) (p
Keywords: Patient safety, nursing, related factors, awareness.